2015
DOI: 10.1097/sla.0000000000001214
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Surgical Coaching Enhances Surgical Skill in the Operating Room

Abstract: Comprehensive surgical coaching enhances surgical training and results in skill acquisition superior to conventional training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(131 citation statements)
references
References 42 publications
1
130
0
Order By: Relevance
“…We have also shown that our dynamic extension of Feature Signatures (DFS) can achieve slightly better retrieval performance than static FS-which are known to work well for content-based retrieval in medical videos [8] -but cannot outperform HMG for our dataset. To the best of our knowledge, we are the first to focus on content similarity search in video archives of gynecologic laparoscopy, with the ultimate goal to support the surgical quality assessment process [11,22]. This work is only a first step in this domain, which would also benefit from semantic content classification approaches, which we want to investigate in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also shown that our dynamic extension of Feature Signatures (DFS) can achieve slightly better retrieval performance than static FS-which are known to work well for content-based retrieval in medical videos [8] -but cannot outperform HMG for our dataset. To the best of our knowledge, we are the first to focus on content similarity search in video archives of gynecologic laparoscopy, with the ultimate goal to support the surgical quality assessment process [11,22]. This work is only a first step in this domain, which would also benefit from semantic content classification approaches, which we want to investigate in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Additional error analysis allows the detection of the surgeon's specific strengths and respective weaknesses. The application of this kind of post-hoc video analysis of surgical videos through comprehensive surgical coaching [11] significantly improves the performance of trained surgeons [9,16,32].…”
Section: Related Workmentioning
confidence: 99%
“…The few publications on coaching for surgeons are quite recent and emphasize performance improvement in practitioners as illustrated in the Gawande example. [42][43][44] However, if the principles of effective coaching can be successfully applied to practicing surgeons with improvement in operative proficiency, extrapolation to resident education would be logical and rational.…”
Section: Teaching Operative Skillsmentioning
confidence: 98%
“…There is increasing interest in mentoring and coaching to improve technical and cognitive skills such as judgment and DM, 48,49 including the potential of procedural videos to be used for safe and timely coaching. 48,49 Specifically, the current repository of operative videos coupled with recorded expert decisions can now be used to better train and assess residents in operative DM. Residents can now be subjected to these operative scenarios and their judgment compared and contrasted with the operative decisions of the expert panel.…”
Section: Discussionmentioning
confidence: 99%